One true loves - Reid, Taylor Jenkins (New York : Washington Square Press, 2016)
Emma and Jesse, high school sweethearts, marry and build a life for themselves, far away from the expectations of their parents in Massachusetts. They travel the world, live life to the fullest, and seize every opportunity for adventure. On their first anniversay, Jesse is on a helicopter when it goes missing over the Pacific ocean. Just like that, he is gone forever. Emma quits her job and moves back to Massachusetts in an effort to put her life back together. Years later, Emma meets Sam, an old friend, and finds herself falling in love again. They get engaged, and Emma feels like she has a second chance at happiness. Then, Jesse is found, alive. With a husband and a fianc Ěmma must decide who she is and what she wants. She knows she must listen to her heart, although she's not sure what it is saying.
Keywords: Triangles (Interpersonal relations) -- Fiction; Man-woman relationships -- Fiction; Mate selection -- Fiction; Love stories